Reflection of Cultural Policy in Business on the Example of Austria - E. I. Boiko (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2019)
The article raises the issue of the mutual influence of national culture and state cultural policy and business models adopted in the state. Based on the postulate of a special cultural environment prevailing in Austria, the author analyzes how business develops in this environment, how brands and firms with global significance function. The article also attaches great importance to such topics as social responsibility of business, charity, international economic relations, the history of successful business projects. The author does not ignore the complex topics about problems in the economic and social spheres, offering to look for their solution in the same cultural policy. The main method for analyzing information is content analysis, and the Internet is used as the source of information — the most dynamic resource, reflecting all the changes in the studied areas, Russian-language journalism and literature. The main topic of the article is the proof of the possibility of coexistence of the strategy of preserving and multiplying cultural baggage with the desire to achieve economic benefits and personal success. The author gives various examples of the possibility of their coexistence in the framework of a single state policy, proposing the following thesis as the main conclusion from the article: “business is formed in a certain cultural paradigm that influences it, but which, when it reaches a certain value, begins to influence the environment”.